PERAN END CHILD PROSTITUTION, CHILD PORNOGRAPHY & TRAFFICKING OF CHILDREN FOR SEXUAL PURPOSES (ECPAT) INDONESIA DALAM MENANGANI KASUS PELECEHAN SEKSUAL DIGITAL TERHADAP ANAK DI INDONESIA - Dini, Annisa Nurul Rachma (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Cases of digital sexual abuse against children in Indonesia have increased significantly along with the rapid development of technology and internet access. Low levels of digital literacy among children and parents, lack of regulations that specifically regulate digital sexual abuse of children, and weak coordination between the government, law enforcement, and digital platforms have resulted in many cases going unreported or not being handled properly. There is a nongovernmental organization called ECPAT Indonesia that focuses on cases of digital sexual abuse against children. This research uses a qualitative method with a case study approach and the use of Lewis's Non-Governmental Organization theory, NGOs play a role as implementers, catalysts, and partners. This study will analyze the role of ECPAT Indonesia in dealing with digital child sexual abuse in Indonesia in accordance with its role as an NGO. Primary data was obtained from online interviews with representatives of ECPAT Indonesia and the Internet Watch Foundation (IWF). Secondary data was obtained from journals, books, internal organizational documents, and other related websites. The results of the research show that ECPAT Indonesia plays an important role in advocacy, education, and cooperation with various stakeholders in dealing with online child sexual exploitation. ECPAT Indonesia actively collaborates with various government and non-government institutions, conducts public campaigns, and provides assistance to child victims of online sexual abuse. ECPAT Indonesia continues to strive to protect children in the digital world so that prevention and handling can run effectively. Keywords: ECPAT Indonesia, Digital Sexual Abuse, Child Protection, NGO, Child Sexual Exploitation.